CINDERELLA COMPLEX: APA KAITAN KONSEP DIRI DAN POLA ASUH BERWAWASAN GENDER? - Hilwa, Hilwa; Arya, Lutfi; Syanti, Wanda R. (Jurnal Psikologi, 2024)
Women entering early adulthood will face various developmental demands and challenges. These demands and challenges require early adult women to be independent and no longer dependent on other people. This research is a new finding that aims to reveal the relationship between self-concept and gender-oriented parenting independently and simultaneously with the Cinderella complex in 312 early adult women. The measuring instruments in the research are the self-concept scale, the gender-oriented parenting style scale, and the Cinderella complex scale. The data analysis technique used multiple regression and the results obtained were that self-concept and gender-oriented parenting were simultaneously related to the Cinderella complex with an effective contribution of 32.2% (23% contribution of self-concept & 29.4% contribution of gender-oriented parenting). This research supports external factors as factors that have a greater influence on the Cinderella complex based on a comparison of correlation coefficient values and effective contribution. These findings can be a basis for consideration for further research related to the Cinderella complex theme and the formulation of interventions for women with Cinderella complex syndrome